2021
DOI: 10.1177/0003134820972985
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative Endovascular Balloon Occlusion of Aorta: A Systematic Review

Abstract: Background The data on resuscitative endovascular balloon occlusion of the aorta (REBOA) use continue to grow with its increasing use in trauma centers. The data in her last 5 years have not been systematically reviewed. We aim to assess current literature related to REBOA use and outcomes among civilian trauma populations. Methods A literature search using PubMed, EMBASE, and JAMA Network for studies regarding REBOA usage in civilian trauma from 2016 to 2020 is carried out. This review followed preferred repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…REBOA may also be used as an adjunct to PPP to stem temporary bleeding [ 224 , 225 ]. The available data suggest that REBOA can temporarily improve haemodynamics [ 226 , 227 ]. The evidence demonstrating that REBOA improves survival is conflicting [ 228 230 ] and REBOA is associated with potentially significant complications [ 224 , 230 ].…”
Section: Resultsmentioning
confidence: 99%
“…REBOA may also be used as an adjunct to PPP to stem temporary bleeding [ 224 , 225 ]. The available data suggest that REBOA can temporarily improve haemodynamics [ 226 , 227 ]. The evidence demonstrating that REBOA improves survival is conflicting [ 228 230 ] and REBOA is associated with potentially significant complications [ 224 , 230 ].…”
Section: Resultsmentioning
confidence: 99%
“…Full texts were retrieved and assessed by the same reviewers independently. We also screened the reference lists of publications and previous systematic reviews for additional records 5,8–12 . Disagreement was resolved after review by a third reviewer (N.A.…”
Section: Methodsmentioning
confidence: 99%
“…We also screened the reference lists of publications and previous systematic reviews for additional records. 5,[8][9][10][11][12] Disagreement was resolved after review by a third reviewer (N.A. and E.G.W.).…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Studies on REBOA have not consistently found a mortality benefit [6]. Mortality may not be the appropriate endpoint to assess this modality.…”
Section: Introductionmentioning
confidence: 98%